Impact heat driven volatile redistribution at Occator crater on Ceres as a comparative planetary process - P. Schenk (Nature Portfolio, 2020)
Dawn mission’s second extended phase provided high resolution observations of Occator crater of the dwarf planet Ceres. Here, the authors show stereo imaging and topographic maps of this crater revealing the influence of crustal composition on impact related melt and hydrothermal processes, and compare features to those on Mars, Earth and the Moon.